2020
DOI: 10.1523/eneuro.0211-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Elements Inserted into AAVs Confer Preferential Activity in Cortical Interneurons

Abstract: Cortical interneuron (CIN) dysfunction is thought to play a major role in neuropsychiatric conditions like epilepsy, schizophrenia and autism. It is therefore essential to understand how the development, physiology, and functions of CINs influence cortical circuit activity and behavior in model organisms such as mice and primates. While transgenic driver lines are powerful tools for studying CINs in mice, this technology is limited in other species. An alternative approach is to use viral vectors such as AAV, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 85 publications
(176 reference statements)
0
12
0
Order By: Relevance
“…Targeted delivery of transgenes, encoding fluorescent reporters, functional sensors/effectors, supplemental proteins to rescue imbalanced cell functions or genome editors, to specific cell populations enables us to untangle complex biological circuits and offers promise as a therapeutic approach [1][2][3][4] . Targeting strategies include transgenic animal models, engineered viral vectors with biased tropisms [5][6][7][8][9][10][11][12][13] , gene regulatory elements (for example, promoters [14][15][16][17][18] , enhancers [19][20][21][22][23][24][25] and/ or microRNA target sites [26][27][28] ) and various delivery routes. These methods, often used in combination 2,27 , have granted selective access to a few cell types but are still far from covering most molecularly distinct cell populations.…”
mentioning
confidence: 99%
“…Targeted delivery of transgenes, encoding fluorescent reporters, functional sensors/effectors, supplemental proteins to rescue imbalanced cell functions or genome editors, to specific cell populations enables us to untangle complex biological circuits and offers promise as a therapeutic approach [1][2][3][4] . Targeting strategies include transgenic animal models, engineered viral vectors with biased tropisms [5][6][7][8][9][10][11][12][13] , gene regulatory elements (for example, promoters [14][15][16][17][18] , enhancers [19][20][21][22][23][24][25] and/ or microRNA target sites [26][27][28] ) and various delivery routes. These methods, often used in combination 2,27 , have granted selective access to a few cell types but are still far from covering most molecularly distinct cell populations.…”
mentioning
confidence: 99%
“…So far, not much is known about its function, but it has been shown that Arl4D is involved in neurite growth [ 70 ], adipogenesis [ 71 ] and actin remodeling [ 72 ]. In adult mice, Arl4d is expressed in neocortical layer 1 and hippocampus, mostly in cortical interneurons (CIN), whose loss or alteration have been related to neurological disorders such as autism, schizophrenia, and epilepsy [ 73 ]. Interestingly, both DMRs are directly or indirectly related to neurological disorders such as ASD.…”
Section: Discussionmentioning
confidence: 99%
“…AAV is gaining traction as a powerful method for enhancer-driven, cell-type-specific manipulations 15,16,66 .…”
Section: Discussionmentioning
confidence: 99%